Development of E-Learning on Abundance of Elements Based on Self Direct Guided Inquiry Learning in Senior High School - Arizona Zamri; Siska Candra Ningsih; Sri Herlina; Shirley Shirley (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2023)
This study meant to describe how to e-learning that base on guided inquiry can improve self-direct of student in senior high school to learn about abundance of elements. Abundance of elements is one of core material in senior high school, but this material difficult to understand for the students. It cause of its material need some understanding and analyzing to differentiate one element to the others. The research and development of learning module by using 4D models. The phase Define, Design, Develop and Disseminate. To know the quality of the module we use validation and practicality test. The validated by four validator and for practicality by ten students of SMAN 5 Payakumbuh. From that test we get result for content validity is 0.85 and 0.83 in structure. The practicality test result is 0.80. From that result we can get conclusion that e-learning developed is valid and practical.